A Question of Design: Strategies for Embedding AI-Driven Tools into Journalistic Work Routines. Issue 3 (16th March 2023) - Gutierrez Lopez, Marisela; Porlezza, Colin; Cooper, Glenda; Makri, Stephann; MacFarlane, Andrew; Missaoui, Sondess
Abstract: With the promise of AI, the use of emerging technologies in journalism has gained momentum. However, the question of how such technologies can be interwoven with newsroom practices, values, routines, and socio-cultural experiences is often neglected. This article investigates the ways in which AI-driven tools are permeating newswork and design strategies for blending technological capabilities with editorial requirements. We followed a multi-method approach to investigate the deployment of AI in news production at two London newsrooms: (1) a design ethnography at the BBC with journalists and technologists, and (2) interviews with journalists at The Times. Our findings show that while journalists are generally open to try AI-driven technologies that benefit their work, technologists struggle to integrate them into journalistic workflows. The consensus was that human judgement is required to make complex decisions in journalism and that journalistic values should be prioritised in AI tool design. We claim that AI tools need to fit with professional practices and values in journalism in order to be fully accepted as an editorial tool. Embedding new technologies into journalistic workflows requires therefore a close collaboration between journalists and technologists, and a sociotechnical design that blends in work routines and values.